The Lithium-ion Battery Standby Power of Wind Turbine Pitch System. (May 2017) - Bixiao, Guo; Jian, Wu; Ju, Qun; Qingjun, Han
Abstract: In this paper, the use of lithium-ion batteries as a backup power of pitch system of wind turbine is proposed. I designed the battery management system based on DSP28335 including the hardware and software of the system. By the use of CAN communication and voltage current Hall sensors, the system realizes the collection of cell voltage, total voltage, charge discharge current parameters of the batteries. I use Ampere-time integration and other methods to estimate the battery the SOC of batteries when it is charging or discharging. During the charging and discharging time, the data of ICA is recorded. Finally, the function of battery management system was verified by experiments.